Nicotinamide adenine dinucleotide supplementation fails to enhance anesthetic recovery in rodents - Candida L. Goodnough; July Montoya; Erica B. Cartusciello; Erin L. Floranda; Eric R. Gross (Scientific Reports)
Abstract Nicotinamide Adenine Dinucleotide (NAD+) is implicated in bioenergetics, DNA repair, and senescence. Depletion of NAD+ is associated with aging and neurodegenerative disease, prompting a growing interest in NAD+ supplementation. With rising over-the-counter use of NAD, understanding their impact on anesthetic recovery becomes essential. This study investigates the effect of NADH, a common NAD+ precursor, on anesthesia in rodents. Baseline and post-anesthesia (1.5% isoflurane) open field and Y-maze activity were recorded in adult male and female C57BL/6 mice (n = 8–10/group). NADH (150 mg/kg, intraperitoneal) or vehicle (0.9% normal saline) were given at baseline or during anesthesia. The NADH-treated group exhibited a significant decrease in open-field activity relative to vehicle-treated. This diminished activity was reflected in reduced distance travelled and average velocity after emergence from anesthesia in the NADH-treated group. NADH treatment did not improve Y-maze performance after anesthesia, partly related to reduced locomotor activity in the NADH-treated group. This study demonstrates that NADH does not appear to hasten recovery from anesthesia. Instead, there was a depression in open-field activity and no change in Y-maze performance with NADH supplementation, indicators of locomotive and cognitive recovery in rodents. The broad implications of NAD+ in aging are likely to shape supplementation trends, highlighting the importance of understanding the potential influence of administering NAD+ on anesthetic sensitivity and recovery.